Assessment of the effect of calcium on the anti-inflammatory activity of etoricoxib in albino rats - Naringrekar, Sonali; Mamtora, Jayesh (International Journal of Basic & Clinical Pharmacology, 2021)
Background: It would be worthwhile to investigate if it is possible to obtain an anti-inflammatory effect with a lower dose of etoricoxib after it has been combined with calcium, the effect of which is equivalent to higher dose of etoricoxib. Hence the aim was to study effect of calcium and calcium gluconate on the anti-inflammatory activity of etoricoxib. Methods: Animals were distributed in five groups each group containing six rats. Experiments were conducted between 9:00 to 16:00 hours. All animal procedures were performed in accordance with the recommendations for proper care and use of laboratory animal .The doses of drugs employed in the study were based upon the human dose after conversion to that of rat. Results: The results of present study indicate that calcium gluconate (50 mg/kg) combined with etoricoxib (5 mg/kg) possesses significant anti-inflammatory property both in acute and subacute models of inflammation which was comparable to that of etoricoxib (8 mg/kg). Conclusions: From the present study it is concluded that calcium gluconate (50 mg/kg) possesses an anti-inflammatory activity. Lower dose of etoricoxib (5 mg/kg) if combined with calcium gluconate (50 mg/kg) can produce significant anti-inflammatory effect. The advantages of such combined preparations are obviously a reduction in the dose of etoricoxib that could still produce significant anti-inflammatory action and a possible protection against COX -2 inhibitor induced prothrombotic events. It is worthwhile to evaluate such preparations through clinical trials.